The Impact of Social, Psychological, and Economic Factors on Unemployment among Graduates of Higher Institutes: A Field Study at the Higher Institute of Science and Technology, Qasr Al-Akhyar: The Impact of Social, Psychological, and Economic Factors on Unemployment among Graduates of Higher Institutes (Journal of Humanitarian and Applied Sciences, 2026)
This study aimed to analyze the impact of social, psychological, and economic factors on unemployment among graduates of higher institutes, assess the extent to which these factors contribute to explaining the phenomenon, examine differences according to demographic variables, and predict unemployment levels. The study adopted a descriptive-analytical approach and utilized a questionnaire consisting of four dimensions. The questionnaire was administered to a sample of 150 graduates. Various statistical techniques were employed, including Pearson’s correlation coefficient, the independent samples T-test, one-way analysis of variance (ANOVA), and multiple linear regression analysis. The findings revealed statistically significant positive relationships between the three factors and unemployment. Economic factors exerted the strongest influence, followed by psychological factors and then social factors. The results also indicated significant differences attributable to marital status, academic specialization, and year of graduation, whereas no significant differences were found with respect to gender, age, or place of residence. Furthermore, the multiple regression analysis demonstrated that these factors collectively explained 74% of the variance in unemployment, confirming their predictive power. Based on these findings, the study recommends strengthening employment policies, enhancing the alignment between educational outcomes and labor market requirements, and providing greater psychological and social support for graduates.
Keywords: Unemployment; Higher Institute Graduates; Social Factors; Psychological Factors; Economic Factors